The complete chloroplast genome sequence of Achimenes cettoana (Gesneriaceae) - Li, Shu (Mitochondrial DNA B Resour, 2021)
Achimenes Pers. is well known for its floral diversity and widely used in horticulture, but its phylogenetic position is still poorly understood. And most research about the complete chloroplast genome sequence focused on the Old World species; therefore, we think it is necessary to examine taxa of the New World in more detail. This study determined the complete chloroplast genome of Achimenes cettoana H.E. Moore. The cp genome was 153,011 bp in a total length containing two inverted repeats (IRs) of 25,162 bp separated by a large single-copy (LSC) region of 84,669 bp and a small single-copy (SSC) region of 18,018 bp. The whole cp genome of A. cettoana contains 112 genes, including 79 protein-coding genes, 29 tRNA genes, and four rRNA genes. This plastid genome is firstly reported in the New World Gesneriaceae, which will be a valuable resource for future studies on breeding, conservation genetics, and phylogeny of Gesneriaceae.